Factors Affecting the Decision of Tutoring Schools among High School Students in Hatyai District, Songkhla Province - Tongbunmak, Walita; Madiyoh, Abdulhakim (Economics and Business Administration Journal Thaksin University, 2024)
This study aimed to study the factors Affecting the decision of tutoring schools among high school students in the Hatyai district, Songkhla province. A sample group of 400 individuals was used, and data was collected through questionnaires. The data was analyzed using Multinomial Logistic Regression Model. The analysis using Multinomial Logistic Regression revealed that personal factors such as the school attended, gender, grade level, parents' occupations, parents' income, and family size significantly influence the choice of tutoring school among high school students in Had Yai district, Songkhla province. In terms of behavioral factors, the subjects chosen for tutoring, tuition fees, number of days per week attending tutoring, tutoring format, and tutoring style also have a significant impact on the choice of tutoring school among high school students in the Had Yai district, Songkhla province.